Diversity and Traditional Uses of Plant Products in Manipur's Valley Communities - Singh, Napoleon; Tahseen Fatima; Khan, M. R; Dinendra Sharma, L. (Indian Forester, 2026)
This ethnobotanical survey, conducted from April 2024 to March 2025, documented 62 taxa of medicinal and edible plants from the valley districts of Manipur (Imphal East, Imphal West, Thoubal, and Bishnupur), recording their scientific and local names, families, growth habits, plant parts used, preparation modes, and medicinal applications. Trees constituted the largest group (32.26%), followed by herbs (27.42%), shrubs (22.58%), and climbers (17.74%), reflecting the region's agro-mosaic landscape. Fabaceae (12.90%) and Moraceae (8.06%) were the most represented families, alongside moderately represented taxa such as Euphorbiaceae, Meliaceae, and Lamiaceae, with 18 families represented by single species. Leaves were the most frequently used plant part (33.87%), followed by fruits (17.74%) and whole plants (12.90%), indicating a preference for renewable resources that support sustainable harvesting. Juice was the dominant preparation method (27.42%), followed by paste (20.97%) and decoction (17.74%), suggesting a cultural and pharmacological preference for liquid forms. Medicinal uses were most common for digestive disorders (24.19%) and liver-related ailments (20.97%), followed by respiratory problems (16.13%). Several species served dual roles as food and medicine. The findings underscore the strong link between biodiversity, cultural heritage, and traditional healthcare in Manipur's valley districts. While the emphasis on renewable plant parts promotes sustainability, the reliance on certain families and species highlights the need for conservation strategies. Integrating ethnobotanical knowledge with phytochemical and pharmacological research could enhance both community health resilience and biodiversity preservation.